Pengaruh Reward dan Punishment terhadap Produktivitas Kerja Karyawan di PT. Bank Muamalat KCP Stabat - Rizka Novi Arisandi; Azhar Azhar; Anjur Perkasa Alam (AGHNIYA : Jurnal Ekonomi Islam, 2023)
The purpose of this study is to determine the effect of reward and punishment on employee work productivity at Bank Muamalat KCP Stabat and find out how to increase employee work productivity at Bank Muamalat KCP Stabat. The data used in this study is data from the results of questionnaire answers given to BSI Pangkalan Brandan customers. This study used a simple linear regression analysis method using the SPSS computer program version 22.00 and Microsoft Excel 2007. The results showed that both partially and simultaneously the free variables studied, namely reward (X1) and punishment (X2) had a significant effect on the work productivity (Y) of PT employees. Bank Muamalat KCP Stabat. Reward (X1) and Punishment (X2) Work Productivity (Y) of PT. Bank Muamalat amounted to 83.4%, while the remaining 16.6% (100% - 83.4%) was influenced by other variables. Reward and Punishment have a positive direction towards the work productivity of PT. Bank Muamalat KCP Stabat. This means that the greater the compensation given and the better and more comfortable the work environment, the more it will increase the work productivity of PT employees. Bank Muamalat KCP Stabat. Vice versa, if the rewards given are less and the punishments given are not appropriate, it will reduce the work productivity of PT employees. Bank Muamalat KCP Stabat.